PEMIKIRAN PENDIDIKAN RELIGIUS-RASIONAL MUKTI ALI DAN RELEVANSINYA DENGAN DUNIA MODERN - FUAD MAFATICHUL ASROR (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
This study aims to describe Abdul Mukti Ali's thoughts with a religious-rational perspective about school and its importance for the modern world. This study uses a library research strategy. The result of this research is the importance of Abdul Mukti Ali's ideas presented by Mukti Ali and fosters an order of comparative religion. His noble determination in fostering comparative religion studies at IAIN is to revive interfaith discourses to kill doubts and find common belief in the existing contrasts.